Assessment of foot perfusion: Overview of modalities, review of evidence, and identification of evidence gaps. (June 2020) - Rogers, R Kevin; Montero-Baker, Miguel; Biswas, Minakshi; Morrison, Justin; Braun, Jonathan
Patients with critical limb ischemia have nonhealing wounds and/or ischemic rest pain and are at high risk for amputation and mortality. Accurate evaluation of foot perfusion should help avoid unnecessary amputation, guide revascularization strategies, and offer efficient surveillance for patency. Our aim is to review current modalities of assessing foot perfusion in the context of the practical clinical management of patients with critical limb ischemia.